2018
DOI: 10.1002/celc.201801107
|View full text |Cite
|
Sign up to set email alerts
|

Layered TiO2 Nanosheet‐Supported NiCo2O4 Nanoparticles as Bifunctional Electrocatalyst for Overall Water Splitting

Abstract: Exploring the generation of efficient and long‐lasting bifunctional electrocatalysts obtained from low‐cost transition metal oxides is crucial to the optimal production of hydrogen and oxygen by electrocatalytic water splitting. This study aims to demonstrate the applicability of layered TiO2 nanosheets as support for designing electrocatalysts. We have demonstrated the performance by decorating the TiO2 support with NiCo2O4 nanoparticles (NiCo2O4/TiO2) as catalysts for electrocatalytic overall water splitting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 50 publications
3
17
0
Order By: Relevance
“…At an overpotential of 100 mV, the TOF for R-Ni 17 W 3 /WO 2 was up to 0.62 H 2 s −1 . Referring to the nonprecious catalysts previously reported in Figure 4f and Table S1, the Ni 17 W 3 /WO 2 HER performance was better than, or at least comparable to, Ni 4 Mo/GNS (0.11 at 100 mV) 42 and NiCo 2 O 4 (0.17 at 100 mV), 43 which indicated that the S12a). The Ni 17 W 3 alloy particles on Ni 17 W 3 /WO 2 were then etched away using a 0.1 M H 2 SO 4 aqueous solution, as confirmed by XRD (Figure S12b), and the processed samples were referred to as E-Ni 17 W 3 /WO 2 @CP.…”
Section: Methodssupporting
confidence: 52%
“…At an overpotential of 100 mV, the TOF for R-Ni 17 W 3 /WO 2 was up to 0.62 H 2 s −1 . Referring to the nonprecious catalysts previously reported in Figure 4f and Table S1, the Ni 17 W 3 /WO 2 HER performance was better than, or at least comparable to, Ni 4 Mo/GNS (0.11 at 100 mV) 42 and NiCo 2 O 4 (0.17 at 100 mV), 43 which indicated that the S12a). The Ni 17 W 3 alloy particles on Ni 17 W 3 /WO 2 were then etched away using a 0.1 M H 2 SO 4 aqueous solution, as confirmed by XRD (Figure S12b), and the processed samples were referred to as E-Ni 17 W 3 /WO 2 @CP.…”
Section: Methodssupporting
confidence: 52%
“…TiO 2 is cheap, commercially available, nontoxic, and possesses a high mechanical and corrosion resistance. Since its discovery for electrochemical photocatalysis of water at a semiconductor electrode, [ 1–2 ] TiO 2 received a lot of interest and was extensively employed in numerous technologies such as photocatalytic degradation of pollutants, [ 3 ] water splitting, [ 4–5 ] photocathode for the photoelectrochemical hydrogen evolution from water, [ 6 ] solar cells, supercapacitors, lithium‐ion batteries, biomedical devices, [ 7 ] and implants for bone tissue engineering. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…Titanium oxide nanotube arrays (TiO 2 NTAs) have been proposed as a support substrate for superior electrochemical electrodes in many eld because of the unique hollow structure, effective electron transfer pathways, and excellent physical and chemical stability under a wide variety of conditions. [26][27][28][29][30][31][32] More important, the highly ordered TiO 2 NTAs prepared by anodization of Ti substrate exhibits large surface areas, and they do not require additional binders to adhere to Ti substrates. Recently, there are many literatures on the incorporation of noble metal or economic electrocatalysts on TiO 2 NTAs to decrease their overpotential for water splitting, such as RuO 2 doped TiO 2 NT for OER application, amorphous MoS xcoated TiO 2 NTAs and Ru 0.33 Se nanoparticles decorated TiO 2 NTAs for enhanced HER activity.…”
Section: Introductionmentioning
confidence: 99%